Rewriting partnerships : community perspectives on community-based learning - Shah, Rachael W. (Utah State University Press, 2020)
""The first deep analysis of resident experiences of community-based learning. Emphasizing the voices of community residents themselves-adult literacy learners, secondary students, and youth activists who work with students. Introduces Critical Community-Based Epistemologies, an approach to knowledge construction that highlights the voices of community members"--Provided by publisher"--